Developing an educational intervention on dementia diagnosis and management in primary care for the EVIDEM-ED trial - Iliffe, Steve (BioMed Central, 2012)
BACKGROUND: Dementia syndromes are under-diagnosed and under-treated in primary care. Earlier recognition of and response to dementia syndrome is likely to enhance the quality of life of people with dementia, but general practitioners consistently report limited skills and confidence in diagnosis and management of this condition. Changing clinical practice is difficult, and the challenge for those seeking change it is to find ways of working with the grain of professional knowledge and practice. Assessment of educational needs in a practice has the potential to accommodate variations in individual understanding and competence, learning preferences and skill mix. Educational prescriptions identify questions that need to be answered in order to address a clinical problem. This paper reports the development of an educational needs assessment tool to guide tailored educational interventions designed to enhance early diagnosis and management of dementia in primary care, in the Evidence Based Interventions in Dementia in the Community – Early Diagnosis trial. METHODS: A multidisciplinary team, including a lay researcher, used an iterative technology development approach to create an educational needs assessment tool, from which educational prescriptions could be written. Workplace learning was tailored to each practice using the educational prescription, and the method was field-tested in five pilot practices. RESULTS: The educational prescriptions appeared acceptable and useful in volunteer practices. The time commitment (no more than four hours, spread out at the practice’s discretion) appeared manageable. The pilot group of practices prioritised diagnosis, assessment of carers’ needs, quality markers for dementia care in general practice, and the implications of the Mental Capacity Act (2005) for their clinical practice. The content of the educational needs assessment tool seemed to be comprehensive, in that no new topics were identified by practices in the field trial. CONCLUSIONS: The educational needs assessment tool took into account practitioners’ knowledge of the local health and social care systems, reflected the complexity of the diagnostic and care processes for people with dementia, and acknowledged the complexity of the disease process itself.